Proofs

A proof is a series of claims that lead to a conclusion. Some proofs are conditional, which means that the claims can only be made under certain conditions. Click on a statement to see the proof

Log Product Rule
logb(xy) = (logbx) + (logby)

Power Symmetry 2
x(mn) = (xm)n

Move Terms Around
if np = m, then m = pn

Log of an Exponential with Different Bases
logb(xp) = p ⋅ (logbx)

Log of an Exponential
logx(xp) = p

Log of Power Example
log2(23) = 3

Division Substitution
if the following are true:
  • x = i
  • y = j

then i / j = x / y


Division Substitution2
if the following are true:
  • x = i
  • y = j
  • z = k
  • k = i / j

then z = x / y


Changing the Log Base
logbx = (logcx) / (logcb)

Log Base Change Example
log28 = (log108) / (log102)

Transitive Property Application 4
if the following are true:
  • a = b
  • b = c
  • c = d
  • d = e

then a = e


Transitive Property Application 5
if the following are true:
  • a = b
  • b = c
  • c = d
  • d = e
  • e = f

then a = f


Transitive Property Application 6
if the following are true:
  • a = b
  • b = c
  • c = d
  • d = e
  • e = f
  • f = g

then a = g


Transitive Property Application 7
if the following are true:
  • a = b
  • b = c
  • c = d
  • d = e
  • e = f
  • f = g
  • g = h

then a = h


Additive Inverse 2
a + ((-1) ⋅ a) = 0

Greater Than Transitive Property
if the following are true:
  • a > b
  • b > c

then a > c


Transitive Property of Inequality 3
if the following are true:
  • a > b
  • b = c

then a > c


Transitive Property of Inequality 4
if the following are true:
  • a > b
  • a = c

then c > b


Inequality 1
if the following are true:
  • a > b
  • c = a

then c > b


Inequality 2
if the following are true:
  • a > b
  • c = b

then a > c


Double Inequality 1
if the following are true:
  • a > b
  • c = a
  • d = b

then c > d


Distributive Applied
(a + b) ⋅ (b ⋅ (-1)) = ((ab) ⋅ (-1)) + ((bb) ⋅ (-1))

Add Inverse
(ba) + ((ab) ⋅ (-1)) = 0

Equation a
((a + c) + d) + b = ((b + c) + a) + d

Equation
if b + c = 0, then (a + b) + (c + d) = a + d

Difference of Two Squares
(aa) + ((bb) ⋅ (-1)) = (a + b) ⋅ (a + (b ⋅ (-1)))

Reorder Terms 9
(b / c) ⋅ c = (bc) / c

Multiplication Theorem
if not (c = 0), then (bc) / c = b

When the Exponent is a Logarithm
b(logbx) = x

Converseofpowersubstitution
if bm = bn, then m = n

Inequality Greater Than
if b > a, then b + c > a + c

Simplify 4
(a + b) + (b ⋅ (-1)) = a

Inequality Problem
if x + 4 > 9, then x > 5

Inequality Problem 2
if y3 < 21, then y < 7

Inequality Problem 3
if y ⋅ (-2) < -16, then y > 8

Inequality Problem 4 2
if (x + 10) ⋅ (1 / (-5)) > 3, then x < -25

Inequality Problem 4
if (x + 10) / (-5) > 3, then x < -25


Pages: 192 193